The non-territoriality of an eruv: ritual bearings in Jewish urban life - Bechhofer, Robert Y. G. (Journal of Architecture and Urbanism, 2017)
This paper considers the definition and meaning of an eruv1 as “territoriality without sovereignty” in Jewish tradition (Fonrobert 2005). It begins by exploring the origin and development of the term eruv itself, as well as its applications in different urban settings. It distinguishes between, on the one hand, the “enclosure” of the eruv that is made up of various natural and artificial structures that define its perimeter and, on the other hand, the “ritual community” created by the symbolic collection of bread that is known as eruvei chatzeirot. It suggests that much of the controversy, including legal issues of separation of church and state, as well as emotional issues such as the charge of “ghetto-ization”, surrounding urban eruvin (plural of eruv) may be connected to the identification of the area demarcated by an eruv as a “territoriality”. It argues that the enclosure of an eruv is not in itself religious in nature but rather makes up a completely arbitrary and generic “space”, and that it is only through and on account of the eruvei chatzeirot that this space becomes meaningful as a purely symbolic “place” one day a week (on the Sabbath). In the course of this analysis, it considers the one “weekday” on which an eruv may be significant – the Jewish holiday of Purim – and how on that day it may be a tool by which the area defined as part of a given city may be extended.